2013
DOI: 10.1371/journal.pone.0078407
|View full text |Cite
|
Sign up to set email alerts
|

A Glycolipid Adjuvant, 7DW8-5, Enhances CD8+ T Cell Responses Induced by an Adenovirus-Vectored Malaria Vaccine in Non-Human Primates

Abstract: A key strategy to a successful vaccine against malaria is to identify and develop new adjuvants that can enhance T-cell responses and improve protective immunity. Upon co-administration with a rodent malaria vaccine in mice, 7DW8-5, a recently identified novel analog of α-galactosylceramide (α-GalCer), enhances the level of malaria-specific protective immune responses more strongly than the parent compound. In this study, we sought to determine whether 7DW8-5 could provide a similar potent adjuvant effect on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 56 publications
5
52
0
Order By: Relevance
“…7DW8-5 was recently tested by our group in a non-human primate (rhesus monkey) model. In fact, we have tested the adjuvant effect of 7DW8-5 for an adenovirus-based malaria vaccine in rhesus macaques and found that 7DW8-5 could enhance malaria-specific CD8+T-cell responses without showing notable reactogenicity [49]. …”
Section: Discussionmentioning
confidence: 99%
“…7DW8-5 was recently tested by our group in a non-human primate (rhesus monkey) model. In fact, we have tested the adjuvant effect of 7DW8-5 for an adenovirus-based malaria vaccine in rhesus macaques and found that 7DW8-5 could enhance malaria-specific CD8+T-cell responses without showing notable reactogenicity [49]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, Ags that preferentially skew the immune response towards Th1 cytokine production could be useful as vaccine adjuvants and anti-cancer therapeutics (58, 59). Here we have characterized DB06-1, a GSL Ag that differs from the well-studied αGalCer by only a single atom.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, activated iNKT cells reduced the parasitemia by increasing the production of IFNγ in liver (Gonzalez-Aseguinolaza et al, 2000). These findings have stimulated studies to determine if synthetic GSLs that activate iNKT cells could act as adjuvants as part of a malaria vaccine, with some promising preliminary results from a trial in primates (Padte et al, 2013). In the case of the P. berghei ANKA/rodent model of cerebral malaria, even in the absence of αGalCer, iNKT cells from different mouse strains influenced the outcome in terms of Th1/Th2 cytokine polarization, proinflammatory cytokine levels, pathogenesis, and fatality (Hansen, Siomos, Buckingham, Scalzo, & Schofield, 2003).…”
Section: Influenza a Virusmentioning
confidence: 99%